2021
DOI: 10.1186/s12884-021-03598-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of birth weights of neonates of mothers receiving vs. not receiving zinc supplement at pregnancy

Abstract: Background Zinc is an essential element for normal embryogenesis and embryonic and neonatal development. Therefore, we compared the birth weights of neonates born to mothers who consumed zinc supplement during pregnancy with that of neonates born to mothers who did not. Methods In a cross-sectional study, we divided 200 pregnant mothers into two groups: case group (mothers receiving zinc supplement during pregnancy) and control group (mothers not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Zn is essential for embryogenesis and neurogenesis. Deficiency in this element is associated with fetal growth retardation and neurodegenerative disorders (28,(49)(50)(51). It may also promote antimicrobial activity (15,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn is essential for embryogenesis and neurogenesis. Deficiency in this element is associated with fetal growth retardation and neurodegenerative disorders (28,(49)(50)(51). It may also promote antimicrobial activity (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…Due to these concerns, similarly to magnesium and iron, supplementation for both pregnant and lactating mothers is recommended. The average intake is in the range of 9.6-11.2 mg/day ( 51 , 52 ). Another reason to determine the amniotic fluid levels is that oxidative stress, induced by menadione, is further exacerbated by high concentrations (80 µM) of Zn ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and dose-response meta-analysis of observational studies, Zhao et al found that maternal 25-hydroxyvitamin D concentration was closely related to SGA births and each 25 nmol/L increase in 25(OH)D was linked with even a 10% risk reduction of SGA [ 26 ]. Additionally, SGA neonates have significantly lower levels of serum zinc compared to AGA neonates [ 67 , 68 ]. A systematic review by Wilson et al observed a correlation between umbilical cord and maternal blood zinc levels with birth weight.…”
Section: Methodsmentioning
confidence: 99%
“…19 Studi menyebutkan terdapat hubungan langsung antara asupan dan suplementasi zinc terhadap status kecukupan zinc pada serum ibu. 20 Asupan zinc pada makanan sering tidak adekuat karena jumlah zinc dalam makanan tidak dapat dipastikan, gangguan penyerapan zinc, dan lain-lain. 20 Selain fungsinya pada kehamilan dan keluarannya, zinc juga diketahui memiliki fungsi menjaga dan meningkatkan sistem imun, mempercepat penyembuhan luka, dan mempercepat penyembuhan penyakit, seperti diare dan common cold.…”
Section: Asam Folatunclassified
“…20 Asupan zinc pada makanan sering tidak adekuat karena jumlah zinc dalam makanan tidak dapat dipastikan, gangguan penyerapan zinc, dan lain-lain. 20 Selain fungsinya pada kehamilan dan keluarannya, zinc juga diketahui memiliki fungsi menjaga dan meningkatkan sistem imun, mempercepat penyembuhan luka, dan mempercepat penyembuhan penyakit, seperti diare dan common cold. 21 Studi review Cochrane terhadap 21 penelitian randomized controlled trial (RCT) menyebutkan bahwa suplementasi zinc pada wanita hamil dapat menurunkan risiko terjadinya kelahiran prematur (RR 0,86; 95% CI 0,76-0,97).…”
Section: Asam Folatunclassified